Pengaruh dari Kedaulatan Negara Terhadap Pelaksanaan Mekanisme Kerjasama ASEAN dalam Pemberantasan Terorisme - Budi Hermawan Bangun (Universitas Negeri Semarang, 2019)
This paper focuses on the sovereignty of the state and its influence on the implementation of ASEAN cooperation mechanisms in combating terrorism.State sovereignty tends to obstruct the counter-terrorism effort. The difficulty of gaining consensus has temporarily encouraged member countries to enable bilateral or trilateral framework options, which are less productive of regional insight development efforts. The consensus mechanism causes in any degree the handling of terrorism issues in ASEAN will only be possible if the parties agree. This is what then makes the implementation of the agreement in ASEAN to be slow and even not run.